2008
DOI: 10.1063/1.2826351
|View full text |Cite
|
Sign up to set email alerts
|

Atomic partition of the optical rotatory power of methylhydroperoxide

Abstract: Articles you may be interested inOn the determination of the diagonal components of the optical activity tensor in chiral molecules J. Chem. Phys. 140, 074105 (2014) We applied a methodology capable of resolving the optical rotatory power into atomic contributions. The individual atomic contributions to the optical rotatory power and molecular chirality of the methylhydroperoxide are obtained via a canonical transformation of the Hamiltonian by which the electric dipolar moment operator is transformed to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…They showed that structural parameters are determinant in the calculations, but for metal complexes the results are far off, indicating that chiroptical response properties also are a challenge for metal compounds. Also, the second-order polarisation propagator approximations (SOPPA) [17] and SOPPA with CC singles and doubles amplitudes (SOPPA(CCSD)) [18] have been employed in a previous calculation of the ORP in methyl hydroperoxide (MHP) [19]. A different contribution to the understanding of structure-chiroptical property relationships has been reviewed for both the measurement and computation of chiroptical properties of oriented systems [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that structural parameters are determinant in the calculations, but for metal complexes the results are far off, indicating that chiroptical response properties also are a challenge for metal compounds. Also, the second-order polarisation propagator approximations (SOPPA) [17] and SOPPA with CC singles and doubles amplitudes (SOPPA(CCSD)) [18] have been employed in a previous calculation of the ORP in methyl hydroperoxide (MHP) [19]. A different contribution to the understanding of structure-chiroptical property relationships has been reviewed for both the measurement and computation of chiroptical properties of oriented systems [20].…”
Section: Introductionmentioning
confidence: 99%
“…The second approach, described by some of us [32], uses a canonical transformation of the Hamiltonian to resolve the average ORP of a molecule into atomic contributions, based on the torque formalism for the magnetic dipole moment operator and/or the acceleration gauge for the electric dipole moment operator. This approach has been used for the study of the conformational profile of the ORP of hydrogen peroxide [32], hydrazine [33] and MHP [19]. Corresponding algorithms have been implemented within the SYStems MOdena suite of computer programs [34].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide and its derivatives have been widely used as models to computationally study chiral properties due to their small size, which makes them very adequate for theoretical studies. Thus, their optical rotatory power (ORP) shows a very interesting dependence on the dihedral angle, providing both positive and negative values in the range 0–180°. , The atomic partition of the ORP has been carried out using the acceleration gauge for the electric dipole and the torque formalisms. , The chiral discrimination of the dimers (homochiral vs heterochiral) has been previously studied for several of its derivatives (HOOX, X = H, CCH, CH 3 , CF 3 , t -C 4 H 9 , CN, F, Cl) , and for large clusters of the parent compound. , The coupling constants of some dimers have been calculated to check the possibility of this property to distinguish between homo- and heterochiral complexes . The inclusion of the solvent effect on the chiral discrimination on the dimers of hydrogen peroxide and its methyl derivatives showed that their relative stability could be reversed due to solvation. , …”
Section: Introductionmentioning
confidence: 99%
“…They also investigated a marine natural product called hennoxazole and the absolute configuration of indoline, azetidine, menthols, and menthones . Another atomic decomposition of the OR response was also proposed by Ferraro and co-workers who focused on rather small molecules such as hydrogen peroxide, hydrazine isomers, and methylhydroperoxide . Following this, Autschbach and coworkers , proposed to analyze the OR with localized molecular orbitals (i.e., bond and lone-pair MOs).…”
Section: Introductionmentioning
confidence: 97%
“…44 Another atomic decomposition of the OR response was also proposed by Ferraro and co-workers 45−47 who focused on rather small molecules such as hydrogen peroxide, 45 hydrazine isomers, 46 and methylhydroperoxide. 47 Following this, Autschbach and coworkers 48,49 proposed to analyze the OR with localized molecular orbitals (i.e., bond and lone-pair MOs). They were particularly interested in the large OR of norbornenone, 49 showing that one OR tensor component was enhanced by the coupling between the CC double bond and CO oxygen lone pair.…”
Section: ■ Introductionmentioning
confidence: 99%